Ocorrência, uso de habitats e distribuição de jacarés (alligatoridae) na estação ecológica de Maracá, Roraima, Amazônia brasileira - Souza, Bruno de Campos (2010)
The present study aimed to determine the occurrence, habitat use and distribution of alligators (AIIigatoridae) in the main aquatic environments of the Eastern half of the Maraca Ecological Station and its surroundings, taking into consideration also the transition between the savanna and the forest, in Roraima. Whereas the distribution and diversity of alligators in different habitats may be the product of the environmental diversity, availability of resources and interactions among species, three ecological questions were formulated: (1) are there significant differences in abundance and distribution of alligators between the watercourses located in forest and in savanna (lavrado) areas? (2) and between river, stream and floodplain types of environment? (3) is the estimated abundances of alligators influenced by variation in the water levei? The study area consisted of 22 transects located in the three types of aquatic habitats: river, stream and floodplain. The total length of transects surveyed was 104 km, where 60.8 km were associated to savannas and 44.2 km to forests. The definition of watercourses and its associated vegetation (forest or savanna) was performed by analysis of LANDSAT 5 TM images, using the software ArcGIS 9.3. Abundance was estimated by counting the total number of alligators per kilometer of watercourse sampled. The alligators' counts were dane at night when the location of each alligator was determined by the reflex of its eyes when illuminated, using a boat as an observation plataform. The geographical coordinates of each register was dane with a GPS. Statistical tests were performed with the aid of the program Systat 10.0 with a significance levei of 95% (p <0.05), using non-parametric Mann-Whitney test to compare the abundances between transects associated with the savanna and forest, and Kruskai-Wallis test for three types of aquatic habitats (river, stream and floodplain). The Spearman correlation test was used to verify the relationship between the water levei of rivers and abundance of alligators. Ninety one counts were conducted during six field trips, when 1270 alligators were observed in 477.4 km of aquatic environments. After analyzing the results of statistical tests, it can be concluded that C. crocodilus and M. niger were more abundant in the streams associated with savannas, whereas the species P. trigonatus was more frequently found in transects associated with the forest. Tests for the species P. palpebrosus resulted in no significant differences. Regarding the differential use of habitats, it can be concluded that C. crocodilus and P. trigonatus were more abundant in the habitats of river, while no significant difference were recorded for the other species. The impact of the river water levei on the abundance of alligators showed a negative correlation, i.e. in the dry season, the estimated number of alligators was higher than when the water levei was high.